Evaluation of Food Safety Training Programs in the Food Service Industry in Tanzania - Adil, Akida (International Journal of Food Sciences, 2023)
Purpose: The aim of the study was to investigate evaluation of food safety training programs in the food service industry in Tanzania Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The evaluation of food safety training programs in the food service industry in Tanzania revealed positive outcomes. Training initiatives led to significant improvements in food safety knowledge and practices among restaurant and food establishment staff. Compliance with food safety regulations increased, contributing to a reduced incidence of foodborne illnesses. However, challenges related to resource constraints and long-term sustainability were identified, calling for tailored strategies to address these issues. Overall, food safety training programs were effective in enhancing food safety standards in the Tanzanian food service industry but require ongoing support and adaptation to maintain their impact. Unique Contribution to Theory, Practice and Policy: Health belief model, Social cognitive theory , Theory of planned behavior may be used to anchor future studies on evaluation of food safety training programs in the food service industry in Tanzania. Implement continuous assessment mechanisms within food safety training programs. Encourage policymakers to establish and enforce regulations that require individuals to complete certified food safety training before working in food service roles.